Cover Image, Volume 43, Issue 8. (11th June 2019) - Lee, Jeongmook; Kwon, Choah; Kim, Jandee; Youn, Young‐Sang; Kim, Jong‐Yun; Han, Byungchan; Lim, Sang Ho
Abstract : The inside front cover image is based on the Research Article Integrated study of experiment and first‐principles computation for the characterization of a corium type ZrO8 complex in a Zr‐doped fluorite UO2 by Jeongmook Lee et al., https://doi.org/10.1002/er.4469 .